2003
DOI: 10.7863/jum.2003.22.6.635
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Diagnosis of Talar Lateral Process Fracture

Abstract: he frequency of fractures of the lateral process of the talus (LPT) has markedly increased because of the expansion of snowboard activity. These lesions are difficult to diagnose, because they have aspecific signs, and standard radiographs do not show the fractures in 50% of cases. Sonography is used more and more in the assessment of ankle trauma, but it is rarely performed for detection of bone fractures. We report a case of a patient in which sonography directly showed an LPT fracture. Case ReportA 32-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 7 publications
0
17
0
2
Order By: Relevance
“…The normal periosteum, depending on its thickness, can sometime difficult to assess by sonography. Due to its tomographic capabilities, sonography can show acute fractures that are difficult to image on radiography and can show a variety of stress fractures . A recent study on sonographic and radiographic capabilities in the early detection of metatarsal stress fractures showed that sonography had sensitivity of 83% and specificity of 76% (correlated with MRI) and that sonography was more sensitive than standard radiography for this purpose …”
Section: Discussionmentioning
confidence: 99%
“…The normal periosteum, depending on its thickness, can sometime difficult to assess by sonography. Due to its tomographic capabilities, sonography can show acute fractures that are difficult to image on radiography and can show a variety of stress fractures . A recent study on sonographic and radiographic capabilities in the early detection of metatarsal stress fractures showed that sonography had sensitivity of 83% and specificity of 76% (correlated with MRI) and that sonography was more sensitive than standard radiography for this purpose …”
Section: Discussionmentioning
confidence: 99%
“…Copercini et al [6] machten darauf aufmerksam, dass sich der Einsatz der Sonographie sich nicht nur auf die Beurteilung von Ligamenten und Weichteilen beschränke. In Fällen, in denen eine PLT-Fraktur nicht auszuschließen ist, aber eine CT-Aufnahme nicht gemacht werden kann oder will, stellt die Sonographie eine gute und kostengünstige Alternative dar.…”
Section: Anamnese Und Diagnostikunclassified
“…In Fällen, in denen eine PLT-Fraktur nicht auszuschließen ist, aber eine CT-Aufnahme nicht gemacht werden kann oder will, stellt die Sonographie eine gute und kostengünstige Alternative dar. Im Fall des Frakturnachweises ist die CT jedoch nicht ersetzbar [6].…”
Section: Anamnese Und Diagnostikunclassified
“…The talus is the second largest bone of the foot . Anatomically, the talus is divided into the head, neck, and body.…”
mentioning
confidence: 99%
“…Fractures of the talus are the second most common site of all tarsal bone fractures . Fractures of the talus may occur at the neck, body, lateral process, talar dome, and posterior process . Fractures of the medial tubercle of the posterior process are relatively rare .…”
mentioning
confidence: 99%